New NICE Guidelines on Sodium Valproate (November 2023) - Amany Elbagoury; Asif Zia (BJPsych Open)
Aims: The audit aims to ensure compliance with the new sodium valproate guidelines published in November 2023, identify areas of deviation from the guidelines, and improve patient safety and outcomes by promoting adherence to best practices.